X-Ray Polarization of the Black Hole X-Ray Binary 4U 1630–47 Challenges the Standard Thin Accretion Disk Scenario - Ratheesh, Ajay (Institute of Physics Publishing, 2025)
A large energy-dependent X-ray polarization degree is detected by the Imaging X-ray Polarimetry Explorer (IXPE) in the high-soft emission state of the black hole X-ray binary 4U 1630–47. The highly significant detection (at ≈50σ confidence level) of an unexpectedly high polarization, rising from ∼6% at 2 keV to ∼10% at 8 keV, cannot be easily reconciled with standard models of thin accretion disks. In this work, we compare the predictions of different theoretical models with the IXPE data and conclude that the observed polarization properties are compatible with a scenario in which matter accretes onto the black hole through a thin disk covered by a partially ionized atmosphere flowing away at mildly relativistic velocities.